POSITIONING DYNAMICS OF DRIVE GEARS WITH HYDROABSORBER - Vyacheslav I. Grishchenko; Maria S. Kilina; Vladimir A. Chernavskiy (Advanced Engineering Research, 2012)
Kinds of liquid dashpots, braking modes are considered. The improvement of the drive dynamic indices by applying the slotted hydraulic damper is shown on the mathematical model.